On-going clinical trials for elderly patients with a hematological malignancy: are we addressing the right end points?†. (23rd January 2014) - Hamaker, M. E.; Stauder, R.; van Munster, B. C.
Abstract : Currently on-going clinical trials in hematological malignancies are unlikely to significantly improve our knowledge of the optimal treatment for older patients as those outcome measures that are of primary importance to this patient population are still included in only a minority of studies. As a scientific community, we cannot continue to simply acknowledge this issue but must all participate in taking the necessary steps to enable the delivery of evidence-based, tailor-made and patient-focused cancer care to our rapidly growing elderly patient population. Abstract : Background: Cancer societies and research cooperative groups worldwide have urged for the development of cancer trials that will address those outcome measures that are most relevant to older patients. We set out to determine the characteristics and study objectives of current clinical trials in hematological patients. Method: The United States National Institutes of Health clinical trial registry was searched on 1 July 2013, for currently recruiting phase I, II or III clinical trials in hematological malignancies. Trial characteristics and study objectives were extracted from the registry website. Results: In the 1207 clinical trials included in this overview, patient-centered outcome measures such as quality of life, health care utilization and functional capacity were only incorporated in a small number of trials (8%, 4% and 0.7% of trials, respectively). Even in trials developed exclusively for older patients, the primary focus lies on standard end points such as toxicity, efficacy and survival, while patient-centered outcome measures are included in less than one-fifth of studies. Conclusion: Currently on-going clinical trials in hematological malignancies are unlikely to significantly improve our knowledge of the optimal treatment of older patients as those outcome measures that are of primary importance to this patient population are still included in only a minority of studies. As a scientific community, we cannot continue to simply acknowledge this issue, but must all participate in taking the necessary steps to enable the delivery of evidence-based, tailor-made and patient-focused cancer care to our rapidly growing elderly patient population.